Development of Anxiety Instruments - Astini, Kadek Lilik; Dharsana, I Ketut; Suranata, Kadek (Bisma The Journal of Counseling, 2020)
This study aimed to determine the acceptability of the development of an anxiety instrument. The method used was research and development. The design was the 4D model design consisting of 4 stages, namely the stage of definition, design, development, and dissemination. However, the last stage, namely the 'the stage of dissemination' was not carried out because of the Covid-19 pandemic. The data analysis to test the content validity of the anxiety instrument product was the Lawshe CVR and CVI formulas. Based on the results of the CVR calculation, the score was between 0.2 and 1. Furthermore, in the CVI calculation results, the score was 0.817. This score implied that the content validity index of the 60 items in the anxiety instrument was very good. At the step of the reliability test accommodated by Alpha Cronbach and calculated using the Microsoft Excel 2010 for Windows program, the score was 0.896. This score indicated that the reliability level of the anxiety instrument was high.